Policy Analysis of Student Final Projects Presented as Scientific Articles - M Aditya Firdaus; Qiqi Yuliati Zaqiah (Yayasan Sahabat Literasi Edukasi dan Publikasi Bandung, 2024)
This study aims to discuss policy analysis, position, objectives, forms and assessment of the final project in the form of scientific articles as the final project in obtaining a bachelor's degree at the faculty of agama Islamic Nusantara Islamic University. This research applies a qualitative approach with descriptive methods and content analysis. The results and discussion of the research show that the form of the final project at the Islamic religious faculty is divided into theses and scientific articles. Students are declared to have passed scientific articles if they have received an LOA letter of acceptance from a reputable journal called SINTA and are heard in the munaqosah trial. This research concludes that students' interest in choosing the final project in the form of scientific articles is not due to the choice of convenience, but rather more essential including identity, recognition, and appreciation. This research concludes that it is not appropriate to think that writing scientific articles is easier, but all students can certainly present it based on the foundation of integrity. So this study recommends findings to policymakers for consideration of continuing alternative final projects